Evaluation of a program to develop the intercultural competence through rhythmic education in Elementary Education - Santiago Pérez Aldeguer (Universidad Autónoma de Baja California, 2013)
The present paper aimed to evaluate the effects of a rhythmic-musical program on the development of intercultural competence in Primary Education. A quasi-experimental study using pretest-postest measurements, was applied on 646 children of Primary Education. The statistical analyses showed significant differences in the experimental group in the variables: knowledge, values, attitudes and behavior. The importance of designing rhythmic educational programs for the development of intercultural competence in different educational contexts is discussed. Keywords: Rhythmic education; intercultural competence; music education; primary school; percussion.